Penguatan Pemahaman Keislaman Masyarakat melalui Pengabdian Berbasis Ushuluddin di Desa Gunung Sari, Kabupaten Tangerang: Strengthening Community Islamic Understanding through Ushuluddin-Based Community Service in Gunung Sari Village, Tangerang Regency - Julia Astuti; Kania Nurul Hidayah; Muhammad Asgar Muzakki; Jaya Rukmana (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This community service program was implemented in Gunung Sari Village, Tangerang Regency, with a focus on strengthening community Islamic understanding through an Ushuluddin-based approach. The program was motivated by limited public understanding of Islamic teachings in a comprehensive manner, particularly in relation to Islamic creed and the application of Islamic values in social life. The objective of this community service was to enhance religious literacy and Islamic understanding through participatory and contextual Islamic mentoring and dialogue. The implementation employed a participatory approach by involving religious leaders, mosque administrators, and community members as the main subjects of the activities. The activities included thematic Islamic discussions, mentoring on Islamic creed, and strengthening moderate and inclusive Islamic values. The results indicate an improvement in community Islamic understanding, the growth of critical awareness in responding to religious information, and increased community participation in religious activities. This program demonstrates that an Ushuluddin-based approach plays a strategic role in building balanced and contextual Islamic understanding at the village level.